Integrative Collective Ijtihȃd of Contemporary Islamic Family Law: A Review of Tanwirul Afkar Magazine by Ma'had Aly Situbondo - Syafi'i, Imam; Jafar, Wahyu Abdul; Nugroho, Irzak Yuliardy; Wagianto, Ramdan; Hikmiyah, Hawa’ Hidayatul (Madania: Jurnal Kajian Keislaman, 2025)
This study examines the development of istinbâṭ al-ahkâm related to the problems of contemporary Islamic family law contained in the Tanwirul Afkar magazine by Ma’had Aly Situbondo. This research is a qualitative research with data analysis using a content analysis approach. As a legal study, this research is included in Normative Islamic Law research by making Islamic legal norms as the object of research. Data were taken from the exploration of Tanwirul Afkar magazine. The results of this study, Ma’had Aly Situbondo carried out the development of istinbâṭ al-ahkâm in order to respond to the problems of Islamic family law so that legal decisions are relevant and in accordance with the demands of modern society today. Istinbâṭ al-ahkâm developed by Ma’had Aly Situbondo with three patterns, first; istinbâṭ al-aḥkâm al-jama’iy bi at-taqsîm, namely collective ijtihâd with division of tasks in tracing the source of legal decisions, second; carrying out scientific integration without being tied to a particular school of thought, and third; the application of ushuli reasoning which makes ushul fiqh, fiqh principles, and maqȃsid al-syarîʿah as tools in analyzing and answering problems. Based on this, Ma’had Aly Situbondo has characteristics or distinctive features in the istinbȃṭ al-aḥkȃm that is developed, namely collective-integrative ijtihâd and the application of ushuli reasoning. Penelitian ini mengkaji pengembangan istinbȃṭ al-aḥkȃm terkait problematika hukum keluarga Islam kontemporer yang terdapat dalam majalah Tanwirul Afkar karya Ma’had Aly Situbondo. Penelitian ini merupakan penelitian kualitatif dengan analisis data menggunakan pendekatan content analysis (kajian isi). Sebagai kajian hukum, penelitian ini termasuk penelitian hukum Islam normatif dengan menjadikan norma-norma hukum Islam sebagai obyek penelitian. Data-data diambil dari eksplorasi majalah Tanwirul Afkar. Hasil penelitian ini, Ma’had Aly Situbondo melakukan pengembangan istinbȃṭ al-ahkȃm dalam rangka merespon problematika hukum keluarga Islam agar putusan hukum relevan dan sesuai dengan tuntutan kehidupan masyarakat modern saat ini. Istinbȃṭ al-aḥkȃm yang dikembangkan Ma’had Aly Situbondo dengan tiga pola, pertama ; istinbȃṭ al-aḥkâm al-jama’iy bi at-taqsîm, yaitu ijtihâd kolektif dengan pembagian tugas dalam pelacakan sumber putusan hukum, kedua; melakukan integrasi keilmuan dengan tidak terikat kepada mazhab tertentu, dan ketiga; penerapan nalar ushuli dimana menjadikan ushul fikih, kaidah fikih, dan maqâsid al-syarîʿah sebagai perangkat dalam menganalisa dan menjawab permasalahan. Dari hal ini, Ma’had Aly Situbondo memiliki karakteristik atau ciri khas dalam istinbâṭ al-aḥkâm yang dikembangkan, yaitu ijtihâd kolektif-integratif dan penerapan nalar ushuli.